Nanoformulations of curcumin and quercetin with silver nanoparticles for inactivation of bacteria - Alavi, Mehran; Adulrahman, Nareen Arif; Haleem, Azad Abduljabar; Al-Râwanduzi, Ahmed Diyar Hussein; Khusro, Ameer; Abdelgawad, Mohamed A; Ghoneim, Mohammed M.; Batiha, Gaber El-Saber; Kahrizi, Danial; Martinez, Fleming; Koirala, Niranjan (Cellular and Molecular Biology, 2022)
Antibiotic resistance in pathogenic bacteria to various types of antibiotics has resulted in the necessity of new effective strategies to get around this problem. In recent investigations, metal or metal oxide nanoparticles specifically silver nanoparticles (AgNPs) have been employed successfully to hinder antibiotic-resistant Gram-negative and Gram-positive bacteria. However, AgNPs at high concentrations have cytotoxicity for eukaryotic cells which, application of other biocompatible materials particularly plant secondary metabolites of curcumin and quercetin to reduce cytotoxicity is a critical affair. These compounds may be used directly or indirectly to produce AgNPs. In this regard, modified NPs by curcumin and quercetin have shown an increased therapeutic effect and biocompatibility and biodegredibility properties. Therefore, here, recent advances and challenges about antibacterial and biocompatibility properties of nanoformulation of AgNPs with curcumin and quercetin are presented.